Assessment of Detection Efficacy of Mycobacterium Tuberculosis in Sputum Samples by Real-Time PCR-Based Method - Upadhyaya, S.K.; Dixit, S.M.; Shrestha, S.; Dangol, S.D.; Pokhrel, D.; Banjara, S.; Shrestha, K.S.; Hengoju, S.; Dahal, B.K. (Kathmandu University Journal of Science Engineering and Technology, 2013)
Tuberculosis (TB) is a major public health problem in Nepal and ranks as one of the most prevalent communicable diseases throughout the country. In Nepal, 45% of the total population is infected with TB, and 40,000 people get TB every year. Twenty thousand new sputum-positive cases are seen annually, with 5000-7000 people dying each year from TB. Thirty sputum samples were collected from Sukraraj Tropical and Infectious Disease Hospital, Teku, Kathmandu, Nepal, and a comparative study of Acid-fast Bacilli (AFB) test and Real-time PCR was conducted separately with the culture test, regarded as the gold standard by WHO. Detection of Mycobacterium tuberculosis through the use of Real-time PCR was found to be higher compared to AFB and culture. The Real-time PCR test showed higher sensitivity (100%) and specificity (94.11%) compared to the AFB test, with sensitivity of 84.61% and specificity of 88.24%. The positive predictive value was found to be 84.61% and 92.86% for AFB and Q-PCR, respectively. The negative predictive value was found to be 88.24% for AFB and 100% for Q-PCR. Our statistics clearly show that TB diagnosis by Q-PCR is highly efficient and reliable over conventional methods of diagnosis, and we recommend its use in the hospitals and clinics of Nepal.